Digitization of Taxation in the Changing Business Environment & Base Erosion & Profit Shifting (Beps) Special Reference to India - Rosario, Shireen; Chavali, Kavita (European Scientific Journal, ESJ, 2020)
The ever-increasing digitization of businesses around the world is forcing tax authorities to re-look at the way they regulate compliance of tax rules by the tax payers and collect more efficiently taxes that are due. Most of the tax laws were framed in the 20th century and may no longer be relevant in the digitized world of the 21st century. This paper looks at the need for enhanced methods of tax administration and collection in view of the digitization of businesses, the threat of Base Erosion and Profit Shifting (BEPS) and the need for rapid digitization of tax administration. The paper also focuses on the role played by the Organization for Economic Cooperation and Development (OECD) and the advancement in tax administration achieved by various countries with special reference to India. It is observed that as many as 115 countries are aggressively moving towards digitization as a result of call by OECD for greater co-operation. India, though not part of the OECD, has implemented many measures, especially bilateral tax treaties with 50 countries and is also earnestly pursuing digitization to improve tax collection.